Pembelajaran Berbasis Poject Vlog di SMK - Rima Fransiska; Nana Supriatna (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The research titled “Vlog Creation Project to Develop Student’s Creativity in History Learning” was based upon researcher experience in tenth-grade computer science class 2 at vocational 1 Soreang which showed the lack of student’s creativity in history learning. This action class research was done through three cycles in which each cycle has three actions, all of them emphasize to John Elliot’s model of research, Elliot’s model consists of problems identification,field survey, implementation, observation and reconnaissance. The purpose of this research is to develop student’s creativity in history learning which, indicators for creative learning are: creative thinking, working creatively with others and the application of their innovation, these have been processed into sub-indicators accordingly. The results show that in history learning, there is an increase of creative in the sub-indicators, this research can be used as a solution for education institutions and teachers alike to make history learning become more developed.